Equity and efficiency aspects of Italian debt reduction - Hans Fehr; Anna Ruocco (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 1997)
This paper examines the distributional and efficiency effects of different debt reduction schemes in Italy. To finance a given deficit reduction path, we introduce the so-called Eurotax and endogenously adjust either the consumption tax rate or lump-sum transfers in order to balance the budget. The analysis is based on a numerically specified overlapping generations model of the Auerbach-Kotlikoff type which distinguishes five different lifetime in-come classes within each age cohort. Our simulations suggest that the debt reduction in Italy will increase the welfare of future generations between 1 and 3 per cent of their lifetime resources. Mainly this is due to the implied reduction in future net tax burdens. However, factor price repercussions as well as efficiency gains might also be substantiaüy beneficial to future generations. Finally, while the Eurotax is clearly progressive, consumption taxation is revealed to be, at least in our model, regressive even in the long run.
Keywords: 330; Haushaltskonsolidierung; Steuerpolitik; Konvergenzkriterien; Generationengerechtigkeit; Steuerwirkung; Wohlfahrtsanalyse; Italien